PERUBAHAN NILAI BUDAYA MASYARAKAT CAP TIKUS DI DESA TALAITAD UTARA KECAMATAN SULUUN TARERAN KABUPATEN MINAHASA SELATAN - Liandry Vanny Lintong (Universitas Sam Ratulangi, 2022)
Indonesia is a country with ethnic diversity. in the world. Each ethnic group has a different social, political, and cultural identity, such as different regional languages customs and traditions, belief systems and so on. Not only rich in culture, but also a country rich in natural resources both in the agricultural sector, fields, and marine products. In North Sulawesi, especially in Minahasa, it is famous for a liquor called